(untitled) (International Journal of Applied Research in Management and Economics, 2018)
Generally, brand equity valuation methods are divided into two categories: qualitative methods and quantitative methods. In the qualitative approach, the main issue is the customer’s view of the brand. Qualitative issues like familiarity, trust, loyalty and etc. and financial issues of the company are like price premiums, legal issues, value-added to products and etc. This project seeks to investigate some of the brand equity valuation models and determining factors affecting it in scientific articles. In order to do this, firstly we searched some related keywords in two scientific databases (Emerald Insight and Science Direct). Then we examined obtained articles and extract the brand valuation models and factors out of them. In the end, after extracting a variety of models and indexes, the experts of a development organization were asked the most important factor affecting brand equity and the result was presented.